Development of voltage sags monitoring and mitigation analysis for cement manufacturing industries - Mohd. Noor, Mohd. Azhar (2008)
Supply voltage sags are one of the power quality problems, which have become a big concern in the recent years. In all types of networks; industrial, commercial and residential, various load devices are utilised, which are very sensitive to voltage sags like examples electronic controls, computers, adjustable speed drives. Many customer experience severe consequences of voltage sags, which can prevent appliances from proper operating and make industrial processes, shut down. An interruption of industrial process due to voltage sag can result in big economical losses and costs. This project investigates the impact of voltage sags on the plant operation in a heavy industry electrical network. Understanding the existing system immunity to voltage sags is essential, and to accomplish that, MATLAB Simulink was used. Actual plant load flow is modelled and simulation result analysed. Area of vulnerability has been determined and system level of sensitivity has been developed. Result shows that equipments weakness not due to voltage sags at 11kV, but mainly due to failure of lower voltage; i.e. control voltage to hold operation during voltage sags. Further investigation is recommended on the low voltage level. From the investigation, proposed mitigation has been suggested and verified by simulation technique.